Swine-Derived Probiotic Lactobacillus plantarum Modulates Porcine Intestinal Endogenous Host Defense Peptide Synthesis Through TLR2/MAPK/AP-1 Signaling Pathway - Wang, Jing; Zhang, Wei; Wang, Sixin; Liu, Hui; Zhang, Dongyan; Wang, Yamin; Ji, Haifeng (Frontiers in Immunology, 2019)
Host defense peptides (HDPs) have antimicrobial as well as immunoregulatory activities and are involved in epithelial innate immune defense. Dietary modulation of endogenous HDP synthesis is an effective way to boost the host innate immune system. This study aimed to investigate the role of the probiotic Lactobacillus plantarum strain ZLP001 in porcine HDP induction and the underlying mechanism. To this end, we evaluated the stimulatory effect of L. plantarum ZLP001 on HDP expression in piglet intestinal tissue in vivo and porcine IPEC-J2 cells and 3D4/31 cells in vitro, and we examined the underlying intracellular signaling pathway in IPEC-J2 cells. L. plantarum ZLP001 treatment increased the mRNA expression of jejunal and ileal HDPs in weaned piglets. In IPEC-J2 and 3D4/31 cells, L. plantarum ZLP001 stimulated HDP expression, but different HDP induction patterns were observed, with the various HDPs exhibiting different relative mRNA levels in each cell line. L. plantarum ZLP001 induced porcine HDP expression through TLR2 recognition as evidenced by the fact that HDP expression was suppressed in TLR2-knockdown IPEC-J2 cells. Further, we found that L. plantarum ZLP001 activated the extracellular signal-regulated kinase (ERK)1/2 and c-jun N-terminal kinase (JNK) signaling pathways, as indicated by enhanced phosphorylation of both ERK1/2 and JNK and the fact that HDP expression was suppressed upon inhibition of ERK1/2 and JNK. Furthermore, L. plantarum ZLP001 activated c-fos and c-jun transcription factor phosphorylation and activity. We conclude that L. plantarum ZLP001 induces porcine HDP expression in vivo and in vitro, and the induction seems to be regulated via TLR2 as well as the ERK1/2/JNK and c-jun/c-fos signaling pathways. Modulation of endogenous HDPs mediated by L. plantarum ZLP001 might be a promising approach to improving intestinal health and enhancing diarrhea resistance in weaning piglets.